Food Security: A Key Component in Promoting Public Health and Nutrition - Khansa Nur Fathiya (CV. AFDIFAL MAJU BERKAH, 2024)
Food insecurity is a significant issue in public health, with individuals and households experiencing insufficient access to food necessary for maintaining a healthy lifestyle. The objective of this article is to explore the role of food security as a critical element in promoting public health and nutrition. This article was written using a qualitative method through a literature review study. Adequate nutrient intake is essential for good health and optimal performance in all areas of life. Inadequate access to nutritious food can weaken the immune system, making individuals more susceptible to infections and diseases. Food insecurity and poor health can create a cycle of poverty and contribute to health disparities within communities. Additionally, food security and mental health are closely related, and a lack of access to affordable and nutritious food can lead to poorer mental health outcomes such as stress, anxiety, and depression. Addressing food insecurity prevents public health crises and contributes to health disparities. Food security is essential for promoting public health and preventing malnutrition. It ensures adequate nutrient intake, enhancing performance and productivity. Addressing food insecurity is crucial for improving overall well-being and promoting a healthier future for individuals and communities.